Temporal Detection and Phylogenetic Assessment of SARS-CoV-2 in Municipal Wastewater - Nemudryi, Artem; Nemudraia, Anna; Wiegand, Tanner; Surya, Kevin; Buyukyoruk, Murat; Cicha, Calvin; Vanderwood, Karl K.; Wilkinson, Royce; Wiedenheft, Blake (Cell reports. Medicine, 2020)
SARS-CoV-2 has recently been detected in feces, which indicates that wastewater may be used to monitor viral prevalence in the community. Here, we use RT-qPCR to monitor wastewater for SARS-CoV-2 RNA over a 74-day time course. We show that changes in SARS-CoV-2 RNA concentrations follow symptom onset gathered by retrospective interview of patients but precedes clinical test results. In addition, we determine a nearly complete (98.5%) SARS-CoV-2 genome sequence from wastewater and use phylogenetic analysis to infer viral ancestry. Collectively, this work demonstrates how wastewater can be used as a proxy to monitor viral prevalence in the community and how genome sequencing can be used for genotyping viral strains circulating in a community. [Display omitted] SARS-CoV-2 RNA concentrations in wastewater correlate with COVID-19 epidemiologySARS-CoV-2 RNA levels in wastewater follow symptom onset by 5–8 daysSARS-CoV-2 RNA levels in wastewater precede clinical PCR test results by 2–4 daysSARS-CoV-2 genome from wastewater can trace phylogenetic origin Nemudryi et al. demonstrate that wastewater can be used to monitor the progression and abatement of SARS-CoV-2 spread at the community level. The authors show a correlation between epidemiological indicators and viral concentrations measured in wastewater. In addition, they infer viral ancestry using a phylogenetic analysis of sequenced SARS-CoV-2 genome(s) from wastewater.